Discrimination - Fisanick, Christina; Gale Group (Detroit, [Michigan] Greenhaven Press, 2011)
Examines the issue of discrimination from a variety of international perspectives.
ch 1. Health discrimination -- ch 2. Gender and sexuality discrimination -- ch 3. Racial and ethnic discrimination -- ch 4. Cultural and religious discrimination.
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Discrimination; Electronic books